Soft autonomous ingestible device for sampling the small-intestinal microbiome - Del-Rio-Ruiz, Ruben; Romualdo da Silva, Debora Regina [UNESP]; Suresh, Hasika; Creasey, Hannah; Asci, Cihan; dos Santos, Danilo M.; Sharma, Atul; Widmer, Giovanni; Sonkusale, Sameer (Elsevier, 2024)
The gut microbiota is linked to many medical conditions, but our understanding is limited by the lack of affordable, non-invasive ways to sample it. Ingestible devices offer solutions, but current models are complex and can suffer from sample contamination. Consequently, we developed a 3D-printed ingestible device that is elastic, lightweight, low cost, and biocompatible. It collects small-intestinal content via pH-triggered sidewall inlets. Elastic microvalves with swellable beads autonomously close the inlets to prevent contamination. Consistent with bench-scale experimentation, tests in animals demonstrate that the bacterial populations recovered by the pills closely resemble the bacterial populations recovered post mortem from the small intestine. In contrast to the fecal microbiota, samples collected by the ingestible devices were more diverse and were characterized by a lower bacterial concentration than is found in feces. Our non-invasive and cost-effective gut sampling device is expected to advance our understanding of the role of the small-intestinal microbiota.
Keywords: 16S amplicon sequencing; 3D printing; DTI-3; gut microbiota; ingestible device; locking microvalves; non-invasive sampling; pill